Smart teams communicate, congregate, collaborate : how to work better together - Crowley, Dermot (Milton, Qld. John Wiley & Sons Australia, Ltd, 2018)
Communicate, congregate and collaborate more effectively than ever. Smart Teams will help your team to go beyond personal productivity to enhance team productivity. Building on the concepts presented in Smart Work, which focuses on personal productivity, this book shows you how to turn unproductive team behaviours that create friction into 'superproductive' behaviours that promote flow. Productivity is, at its core, a leadership issue -- and this book provides practical guidelines that help you build a culture where productivity thrives. Working together can be a drag -- literally. Email noise, unproductive meetings and poorly organised projects can stifle creativity and disrupt everyone's workflow. But by creating team agreements that raise awareness of the negative impact of our behaviours, you build the desire and capability to change. This book is packed with tips, guidelines and expert insights for leaders and managers at any level. {183}Foster a culture of 'superproductivity' {183}Create a set of Smart Team principles to guide cooperation {183}Run fewer, shorter and more effective meetings {183}Collaborate more productively on projects {183}Reduce urgency, interruptions and email noise People want their work to matter, they want to make an impact and they want to do it all with a healthy work-life balance -- productivity is the key to making it all happen. Smart Teams shows you how to implement the culture shift that will allow your team to flourish.
Includes index.
Prof. Sia (Recommending faculty) - Bookfair 2019
Keywords: Teams in the workplace; Leadership; Employee motivation; Teamwork